Effects of the Affordable Care Act Medicaid Expansion on the Compensation of New Primary Care Physicians. Issue 8 (30th August 2022) - Ma, Yanlei; Armstrong, David; Forte, Gaetano J.; Yu, Hao
Abstract : Background: It is well-documented that the Affordable Care Act Medicaid expansion increased health care utilization by low-income Americans. Emerging studies also found that the expansion changed the geographical distribution of new physicians. However, the effect of the expansion on physician compensation has not been studied. Objectives: We aimed to assess how the Medicaid expansion affected the compensation of new primary care physicians (PCPs) and whether the effect differed by specialty, gender, and geography. Research Design: We used a quasiexperimental difference-in-differences design to assess changes in compensation for new PCPs from before to after the Medicaid expansion in states that expanded Medicaid compared with states that did not expand. Subjects: Our study included 2003 new PCPs who responded to the Survey of Residents Completing Training in New York between 2009 and 2018. Measures: Our primary outcome was respondents' self-reported starting salary for their first year of practice. Our secondary outcomes were respondents' self-reported additional anticipated income and incentives they received for accepting the job offer. Results: We found that starting salaries for new PCPs, especially new general internists and family physicians, grew faster in expansion states than in nonexpansion states. In addition, we found that the expansion was associated with a statistically significant increase in receiving additional anticipated income as part of the compensation package for new PCPs practicing in rural areas.